Free-space optics for ultra-high-speed wireless communications - Albergaria, Daniel Ranzal (2020)
Signal distribution through high capacity links is nowadays a requirement that is becoming more crucial than ever. Therefore, the introduction of fifth generation mobile networks lead to the need for high capacity fronthaul and backhaul. Fiber distributions are commonly available in developed countries, however there are some areas that do not sustain this type of resource, such as in areas with low residential user density. To overcome the idea that resources are allocated only in these areas, free space optics (FSO) present a suitable and lower cost solution and can be used in temporary events (e.g. when the fiber is disrupted). Free space optics is an optical type of communication that requires line of sight, where the atmosphere is the transmission medium. Due to changes in the atmospheric conditions, free space optics systems suffer from variable attenuation. In the scope of this work, the atmospheric interaction is the subject of study. To accomplish link optimization, several alternatives are studied, being based on channel prediction along side with probabilistic constellation shaping. A concave mirror together with a positioning system is also used to overcome structure sway and other sources of pointing error. In the lab, the estimation processes are used to produce 64-QAM connection with variable transmission rates between 400 Gbit/s and 500 Gbit/s and the gain from using adaptive modulation is evaluated. In the last stage, an automatic gimbal positioning system is also tested for several control algorithms.